Evaluation of In Vitro Antimicrobial, Antioxidant, and Anti-Quorum Sensing Activity of Edible Mushroom (Agrocybe aegerita) - Aarti Bains; Prince Chawla; Baskaran Stephen Inbaraj (Foods, 2023)
In the present study, ethanol extract obtained from the mycelial culture of Agrocybe aegerita was evaluated for its antioxidant activity as well for its potential to inhibit the virulence factor responsible for quorum-sensing activity and antibiofilm activity of pathogenic Pseudomonas aeruginosa PAO1 strain. The extract of mushroom at different concentrations showed percentage inhibition in a dose-dependent manner for DPPH and nitric oxide assays with the lowest as 38.56 ± 0.11% and 38.87 ± 0.04% at 50 µg/mL and the highest as 85.63 ± 0.12% and 82.34 ± 0.12% at 200 µg/mL. FTIR analysis confirmed the presence of functional group -OH, O-H bending bonds, C=C stretching, pyranose ring, and H-C-H stretch, confirming the presence of phenol, carotenoid, and ascorbic acid. HPLC analysis revealed that the concentration of gallic acid present in the extract is 27.94 mg/100 g which is significantly (p < 0.05) more than the concentration of rutin (i.e., 7.35 mg/100 g). GC-MS analysis revealed the presence of 5-methyl-1-heptanol, 2-heptadecenal, phthalic acid, butyl hept-4-yl ester, 2-dodecanol, benzoic acid, TMS derivative. The extract showed significantly (p < 0.05) more inhibition of pyocyanin (61.32%) and pyoverdine (54.02%). At higher concentrations of mushroom extract, there was a significant (p < 0.05) reduction (56.32%) in the swarming motility of the test organism. The extract showed 72.35% inhibition in biofilm formation. Therefore, it has been concluded from the present study that mushroom extract, which is rich in phenolic compounds interferes with the virulence factor responsible for quorum sensing, thereby inhibiting biofilm formation, and can be utilized as therapeutic agents against multi-drug resistant pathogenic microorganisms.